Demonstration Method Can Increase Student Learning Outcomes In Science Courses With Materials Of The Earth And The Universe Class Vi Elementary School 017 Tambusai - Sumiati Sumiati (STKIP Rokania Pasir Pangaraian, 2022)
This study aims to improve student learning outcomes in science subjects with earth and nature materials with the demonstration method. Observing and assessing all activities of teachers and students during the research process. The classroom action given in this research is the application of the demonstration method to improve student learning outcomes in science subjects in class VI SD Negeri 017 Tambusai. By applying the demonstration method, it can improve the science learning outcomes of grade VI students of SD Negeri 017 Tambusai for the 2019/2020 academic year. The increase in science learning outcomes for grade VI students at SD Negeri 017 Tambusai is very large from the pre-cycle of the first cycle and continued in the second cycle.